The impact of CEO characteristics and political connections on investment efficiency: evidence from an emerging market / Marwan Altarawneh … [et al.] - Altarawneh, Marwan; Wan Ismail, Wan Adibah; Shafie, Rohami; Kamarudin, Khairul Anuar; Zarefar, Arumega (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2023)
This study examined the influence of CEO characteristics including age, gender, honorific title, ethnicity, and founding role on investment efficiency. This study also investigated whether political connections moderated the relationship between CEO characteristics and investment efficiency. The sample included 1,572 firm-year observations from Malaysia during the period–2014-2018. Financial data were retrieved from the Thomson Reuters database, while CEO attributes were collected from corporate annual reports. The findings suggested that firms with more experienced CEOs or Chinese CEOs had a higher investment efficiency. Firms led by experienced CEOs were less likely to engage in underinvestment or overinvestment strategies. Similarly, firms managed by Chinese CEOs exhibited higher investment efficiency but may have a higher tendency to either overinvest or underinvest. Furthermore, this study indicated that politically connected firms mitigate the negative impact of more experienced CEOs and Chinese CEOs on the likelihood of overinvestment. These findings have practical implications for investors by emphasising the importance of considering CEO traits and politically connected firms when making investment decisions.